Pension wealth returns in Danish households - Henrik Yde Andersen; Stine Ludvig Bech; Simone Maria Bonin; Andreas Kuchler (Danmarks Nationalbank, 2023)
We have estimated a new measure of pension wealth gains, covering the working-age population in Denmark during 2015-2022, in collaboration with Statistics Denmark. By linking this new data to the existing income and tax registers at the individual level, we provide a full picture of net financial wealth gains across the age distribution. This lays out the basis for further analysis, e.g., of the impact of monetary policy on net capital gains in Danish households. The data can be accessed through Statistics Denmark's research data portal.
Keywords: 330; Altersvorsorge; Kapitalmarktrendite; Privater Haushalt; Sparen; Altersgruppe; Vermögen; Dänemark